Penerapan Teknologi Irigasi Tenaga Surya Berbasis IoT Untuk Pembedayaan Petani Di Desa Wonokromo Kabupaten Bantul - Hani, Slamet; Santoso, Gatot; Rusianto, Toto; Baodai, Amadeus Rilto; Fauzi, Ridho; Suryandaru, Alfonsus Care (LPPM Universitas Andalas, 2025)
This activity aims to empower farmers in Wonokromo Village, Bantul Regency, through the implementation of irrigation technology using solar power and IoT. The village's population is predominantly farmers who rely heavily on agricultural products, particularly rice and secondary crops, during the dry season. However, one of the main challenges they face is limited water during the dry season, which leads to decreased agricultural productivity. The method used in this activity is designing a Solar Power Plant (PLTS) as an energy source to operate submersible pumps and IoT to support a more efficient and energy-efficient irrigation system. Activities include outreach to farmers about the benefits of renewable energy technology, PLTS and IoT design, and equipment maintenance training. Furthermore, ongoing mentoring is provided to enable farmers to independently manage this system. The results of this activity indicate the need for innovative and sustainable solutions to address these issues. This includes increasing farmer understanding of the use of environmentally friendly technology. An IoT-based solar irrigation system can increase agricultural land productivity by up to 20% and save on fuel purchases, and farmers can monitor their farmland via smartphone. This provides direct financial benefits to farmers and has a positive, sustainable impact on improving the welfare of farmers in Pandes Hamlet.